TGF-β1 promotes human breast cancer angiogenesis and malignant behavior by regulating endothelial-mesenchymal transition - Li, Zi-Xiong; Chen, Jie-Xin; Zheng, Ze-Jun; Cai, Wang-Jing; Yang, Xiong-Bin; Huang, Yuan-Yuan; Gong, Yao; Xu, Feng; Chen, Yong-Song; Lin, Ling (Frontiers in Oncology, 2022)
Background: Endothelial-mesenchymal transition (EndMT) is an important process of angiogenesis, which plays an important role in in tumor invasion and metastasis, while its regulatory mechanisms in breast cancer remain to be fully elucidated. We previously demonstrated that tumor-associated macrophages (TAMs) can induce EndMT in endothelial cells by secreting CCL18 through the activation of the TGF-β and Notch signaling pathways in breast cancer. This study was designed to study the role of EndMT in breast cancer angiogenesis and progression and explore the underlying mechanism. Methods: Immunohistochemistry (IHC) was used to evaluate the expression of microvascular density (MVD) and EndMT markers in breast cancer. TGF-β1 was used to induce EndMT models of differentiated-endothelial breast cancer stem like cells (BCSLCs). In vitro cell migration proliferation and matrigel tube-formation assays as well as in vivo nude mouse tumor-bearing model and nude mouse dorsal skinfold window chamber (DSWC) model were utilized to investigate the effects and explore the mechanism of EndMT induced by TGF-β1 on breast cancer progression. Results: In this study, we demonstrated that the EndMT markers were positively associated with MVD indicating unfavorable prognosis of invasive ductal carcinoma (IDC) patients. Functionally, TGF-β1 promoted migration, proliferation and angiogenesis of differentiated-endothelial BCSLCs by inducing EndMT in vitro and promoted tumor growth and angiogenesis in vivo. Mechanically, we revealed TGF-β1 induced EndMT by activation of TGF-β and Notch signaling pathways with increase of p-Smad2/3 and Notch1 expression. Moreover, we found Snail and Slug were key factors of TGF-β and Notch signaling pathways . Conclusion: Our findings elucidated the mechanism of TGF-β1 in the promotion of angiogenesis and progression by EndMT in breast cancer.